2022
DOI: 10.3389/fcvm.2022.797297
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of N-Terminal Pro-B-Type Natriuretic Peptide and High-Sensitivity C-Reactive Protein in Patients With Previous Myocardial Infarction

Abstract: BackgroundPatients with previous myocardial infarction (MI) have a poor prognosis and stratification for recurrent major adverse cardiovascular events (MACE) among these patients is of considerable interest. N-terminal pro-B-type natriuretic peptide (NT-proBNP) and high-sensitivity C-reactive protein (hs-CRP) are considered to be potential cardiovascular risk factors, but less is known about their prognostic importance in post-MI patients. This study aimed to evaluate the prognostic value of NT-proBNP and hs-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A metaanalysis of 26 relevant studies with 7,877 participants showed that the elevation of hs-CRP could increase MACE risk by nearly 4-fold compared to normal hs-CRP 18 . In contrast, in a study that enrolled 3,306 post-MI patients, hs-CRP was not an independent predictor for recurrent MACE during a 4-year follow-up period after adjusting for NT-pro-BNP 19 . Another study, including 10,020 patients undergoing primary PCI, showed no associations between hs-CRP and adverse outcomes in multivariate regression analyses 20 .…”
Section: Discussionmentioning
confidence: 63%
“…A metaanalysis of 26 relevant studies with 7,877 participants showed that the elevation of hs-CRP could increase MACE risk by nearly 4-fold compared to normal hs-CRP 18 . In contrast, in a study that enrolled 3,306 post-MI patients, hs-CRP was not an independent predictor for recurrent MACE during a 4-year follow-up period after adjusting for NT-pro-BNP 19 . Another study, including 10,020 patients undergoing primary PCI, showed no associations between hs-CRP and adverse outcomes in multivariate regression analyses 20 .…”
Section: Discussionmentioning
confidence: 63%